Indonesian Dairy Industry Perspective Within the ASEAN Economic Community - Atien Priyanti; Tjeppy D Soedjana (Indonesian Center for Animal Research and Development, 2015)
Many of Indonesian main manufacturing industries based on agriculture should be more responsive to the challenging domestic and global strategic environment, including the newly emerging ASEAN economic community (AEC) which will be effectively implemented by the end of 2015. Dairy industry in Indonesia is a very potential business to play significant role in the ASEAN market based on the existing dairy population, feed resources and the number of dairy farmers. Recently, small and medium enterprise (SME) model in Java has been developed for processing milk. They provide higher farm gate prices under partnership agreement which created a good benchmark and business model for the future dairy industry to adopt. This new attractive business environment gives higher return to the farmers as opposed to the tradition of paying low farm gate milk prices. As feed represents 80% of the total production cost, special attention must be given to land availability to increase feed supply in terms of quality and quantity. Consequently, sustainable support from both central and local government is very critical to keep the partnership model between farmers and the SME milk processing. It also opens new opportunity to increase the linkage more closely between producers and milk processing plants.